The effect of supply chain risks management practices on operational performance of pharmaceutical manufacturing companies in Addis Ababa, Ethiopia: Analytical cross-sectional study - Dinku Mechal; Bekele Boche (PLoS ONE, 2025)
Background The efficient movement of pharmaceuticals through various stakeholders to reach customers in the appropriate quantity and at the right time is achieved through supply chain management. However, the intricate nature of supply chain processes poses tremendous supply chain risks and jeopardizing pharmaceutical manufacturing company’s ability. Failure to address these risks can hinder the provision of high-quality health services. However, effective supply chain risk management can foster more resilient and efficient global supply chains. Therefore, this study aimed to investigate the effect of pharmaceutical supply chain risks management practices on operational performance of pharmaceutical manufacturing companies in Addis Ababa, Ethiopia. Methods Analytical cross-sectional study complemented with qualitative method was conducted at pharmaceutical manufacturing companies in Addis Ababa between May-August 2023. One hundred seventy two staffs working in four manufacturing companies included in the study. For quantitative part, pretested a self-administered five-point Likert scale questionnaire was used and analyzed using SPSS® -version 26. Assumptions of linear multivariate regression were checked and the level of significance determined at a 95% CI and p-value <0.05. Nine face to face in-depth interviews with key informants were conducted to gather the qualitative data, and the data were analyzed using thematic analysis technique. Result The study included 172 employees from four manufacturing companies, with a response rate of 97%. The regression analysis revealed that demand (β=-0.191, t = -4.162, p < 0.05) and supply side risks (β=-0.131, t = -2.015, p < 0.05) have a negative effect on the operational performance of manufacturing companies. Holding other variables constant, a one-unit increase in demand and supply side risks results in 19.1% and 13.1% lead to decrease in operational performance of manufacturing companies, respectively. Increasing costs of freight, shortage and fluctuating foreign exchange rate for currency, lack of logistics expertise and organized risks mitigation team were the major challenges for manufacturing company’s operational performance. Conclusion Demand and supply side risks affected the supply chain performance of the manufacturing companies. Furthermore, the increasing costs of freight, shortage of foreign currency, lack of logistics expertise and organized risk mitigation team were the main bottleneck for pharmaceutical manufacturing company’s performance. The study result suggests demand and supply side risks, increasing costs of freight; shortage foreign currency exchange rate and lack of logistics expertise in companies should be given attention by stakeholders to improve operational performance. Furthermore, understanding these risk factors can improve the operational performance of the pharmaceutical industry by influencing policy and industry practices in the larger framework of global supply chain risk management not only one country.